Dying from cancer with COVID-19: age, sex, socio-economic status, and comorbidities. (3rd August 2021) - Strang, Peter; Hedman, Christel; Adlitzer, Helena; Schultz, Torbjörn
Abstract: Background: The COVID-19 pandemic has caused excess deaths (all causes) and has disproportionately affected the elderly with certain characteristics. Objectives: To study how COVID-19 affected cancer deaths regarding age, sex, socio-economic status, comorbidities, and access to palliative care. An additional objective was to study changes in place of care and death. Material and methods: A descriptive, retrospective study of all cancer patients who died during March–May 2020 in the Stockholm region, n  = 1467 of which 278 died with a COVID-19 diagnosis, compared with deaths in 2016–2019. The Stockholm Regional Council's central data warehouse was used. T-tests, 95% CI, Wilcoxon and chi-squared tests were used for comparisons. Results: There were excess cancer deaths compared with 2016–2019 ( p  < 0.001) and patients dying with a COVID-19 diagnosis were older (79.7 vs. 75.9 years, p  < 0.0001), more often male (67% vs. 55%, p  < 0.0001), and had more comorbidities (Charlson Comorbidity Index 1.6 vs. 1.1, p  < 0.0001). Patients with COVID-19 more seldom had access to palliative care (34% vs. 59%, p  = 0.008), had more changes in place of care during the last two weeks of life ( p  < 0.0001) and died more often in acute hospitals (34% vs. 14%, p  < 0.0001). For the subgroup with access to palliative care, the hospital deaths for individuals with and without a COVID-19 diagnosis were 11% and 4%, respectively ( p  = 0.008). Conclusion: Cancer patients dying with a COVID-19 diagnosis were older, more often male, and had more comorbidities. A COVID-19 diagnosis negatively affected the probability of being admitted to specialized palliative care and increased the likelihood of dying in an acute hospital.